Students’ Interest in Learning English Through Belajar Bahasa Inggris with Aco Application - Sukmawati Tono Palangngan; Eka Mulyaningsih (Institut Agama Islam Negeri Palopo, 2019)
The objective of the research was to find out: (1) whether or not the students are interested in learning through Belajar Bahasa Inggris with ACO Application; (2) Students’ perception in Learning English through Belajar Bahasa Inggris with ACo Application. The research was conducted by using mixed method design (Quan-qual) model. The research applied cluster random sampling by taking one class as the sample. The sample consists of 30 students of A3Accounting Class of STIE Muhammadiyah Palopo. The data were collected through questionnaire and supported by interview. The result of the research showed that the students are interested in learning English through Belajar Bahasa Inggris with ACO Application. Furthermore, the students have positive perception toward the application and the most favourable menu in the application is “chat” and “talk.”